2021
DOI: 10.14202/vetworld.2021.2863-2868
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study utilizing different post-breeding treatment regimens in cyclic Arabian mares

Abstract: Background and Aim: Post-breeding treatment is the most common practice in the reproductive management of mares. Oxytocin, uterine lavage, and intrauterine (I/U) antibiotic are usually used as prophylactic therapy. This study aimed to determine the most efficient prophylactic treatment regimen among six treatment protocols applied during natural breeding of cyclic Arabian mares. Materials and Methods: The current study was conducted on cyclic Arabian mares that were subdivided into three age categories (n=968… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the present case, the clinician chose an antimicrobial treatment followed by an antimicrobial prophylactic infusion. Previous studies have demonstrated an increase in pregnancy rates in mares using post-breeding treatment with intrauterine antibiotic infusion (Karam et al, 2021). In opposition, some authors have demonstrated that post-breeding endometritis is a physiological response during the first 48 h after cover and does not necessarily require medical treatment (Karam et al, 2021;Maischberger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case, the clinician chose an antimicrobial treatment followed by an antimicrobial prophylactic infusion. Previous studies have demonstrated an increase in pregnancy rates in mares using post-breeding treatment with intrauterine antibiotic infusion (Karam et al, 2021). In opposition, some authors have demonstrated that post-breeding endometritis is a physiological response during the first 48 h after cover and does not necessarily require medical treatment (Karam et al, 2021;Maischberger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an increase in pregnancy rates in mares using post-breeding treatment with intrauterine antibiotic infusion (Karam et al, 2021). In opposition, some authors have demonstrated that post-breeding endometritis is a physiological response during the first 48 h after cover and does not necessarily require medical treatment (Karam et al, 2021;Maischberger et al, 2008). This endometrial inflammation is caused by components directly introduced into the uterus of mare, including semen, bacteria and other debris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uterine lavage by using normal saline after mating is often employed in stud farms because of its ability to increase the tone of uterine muscular layer and its effect in clearing microorganisms, spermatozoa, inflammatory cells and debris from the uterine lumen, as these have been found to contribute to early embryonic death in mares [ 121 ]. Use of lactated Ringer’s solution has also been advocated [ 122 ], whilst the use of iodine povidone solution has not become widely applied, as it might cause local inflammation [ 123 ] and reduced expression of endometrial progesterone receptors, hindering fertility [ 124 ].…”
Section: Therapeuticsmentioning
confidence: 99%
“…A potential benefit of oxytocin administration after mating or artificial insemination refers to the increase of contractions of uterine muscles to eliminate excessive spermatozoa, as well as bacteria that might have invaded into the uterus at that time. Oxytocin is used because of its contractile action on the myometrium that would accelerate uterine involution and mucosal degeneration [ 121 ]. However, at later stages during gestation, the increased uterine contractility may cause adverse effects to the foetus borne, hence caution must be applied when administering to mares the correct oxytocin dose according to specific situations [ 172 ].…”
Section: Approaches To Circumvent Antibiotic Resistancementioning
confidence: 99%